The Effect Of Family Support On The Recovery Of Postpartum Mothers Based On Matrilineal Culture In Disaster Risk Areas - Haspita Rizki Syurya Handini; Elda Yusefni; Yefrida Rustam; Neni Fitra Hayati (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Backgrounds: The incidence of maternal death during pregnancy and the puerperium is high and has not been resolved. Many factors affect the recovery of postpartum mothers, among which the main factor is family support. The purpose of this study was to examine the effect of family support on the recovery of postpartum mothers based on the matrilineal culture in disaster-affected high-risk areas. Methods: This type of research is quantitative with a cross-sectional study design. This research was conducted in the independent practice of midwives in Padang City and Pesisir Selatan Regency. The population of this study was postpartum mothers whose samples were taken by consecutive sampling, totaling 140 people. Univariate analysis was conducted in the form of frequency distribution and mean, while bivariate analysis used the Chi-square test. Results: The results of the study found that 61.4% received good support from their husbands, 63.6% received good support from their parents, 73.6% had normal physical recovery and 2.4% had risky physical recovery. There is an influence of the husband's support and family support on the recovery of postpartum mothers both physically and psychologically (p-value = 0,000). Conclusion: The support of the husband and parents has a positive effect on the recovery of postpartum mothers, both physically and psychologically. There is a need for counseling and providing knowledge to families about the importance of family support in the recovery process during the postpartum period.